## How is the formula of a3 b3 derived?

What is the formula for (a3 – b3)?

- Answer: (a3 – b3) = (a – b)(a2 + b2 + ab) Let us prove this by considering a = 4 and b= 2 then. (43 – 23) = (4 – 2)(42 + 22 + 4 × 2) LHS = (2)(28)
- LHS = 56. RHS = (a – b)(a2 + b2 + ab) RHS = (4 – 2)(42 + 22 + 4 × 2)
- RHS = 56. ∴ LHS = RHS. (a3 – b3) = (a – b)(a2 + b2 + ab) Hence the proof.

## What is ABC 3abc degree?

From the given expression, we can find that for ‘a’, ‘b’, ‘c’ collectively has the highest power is 1. Hence the highest degree of the given expression is 1.

**What is the identity of a2 b2 c2?**

a2 + b2 + c2 formula is read as a square plus b square plus c square. Its expansion is expressed as a2 + b2 + c2 = (a + b + c)2 – 2(ab + bc + ca).

**What is #3 stone used for?**

#3. Crushed stone #3 includes stone between 1/2 and 2 inches. This material is a great choice for railroad projects and those that require drainage.

### What size is rip rap rock?

Riprap describes a range of rocky material placed along shorelines, bridge foundations, steep slopes, and other shoreline structures to protect from scour and erosion. Rocks used range from 4 inches to over 2 feet.

### What are some simple factors for a^3 + b^3+c^3?

The factors for a^3 + b^3 = [a+b] [a^2-ab+b^2] , I don’t know of any simple factors for a^3+b^3+c^3 , Computer scientist for 11+ years and passionate about math since childhood. , Just interested in math is all. Kinda a hobby. You have it right there: a^3 + b^3 + c^3. That is simplified as far as you can go.

**What is the value of (A3 – B3)?**

Answer: (a 3 – b 3) = (a – b) (a 2 + b 2 + ab) Let us prove this by considering a = 4 and b= 2 then (4 3 – 2 3) = (4 – 2) (4 2 + 2 2 + 4 × 2)

**What is the formula for a 3 + B3?**

a 3 − b 3 = (a − b) (a 2 + b 2 + ab) a 3 + b 3 = (a + b) (a 2 + b 2 − ab) (a + b + c) 3 = a 3 + b 3 + c 3 + 3 (a + b) (b + c) (c + a) a 3 + b 3 + c 3 − 3abc = (a + b + c) (a 2 + b 2 + c 2 − ab − bc − ac)

## What is the formula for a 3 cube equation?

Cube Formulas. (a + b) 3 = a 3 + b 3 + 3ab(a + b) (a − b) 3 = a 3 – b 3 – 3ab(a – b) a 3 − b 3 = (a − b) (a 2 + b 2 + ab)